Diversification and recurrent adaptation of the synaptonemal complex in Drosophila. - Rana Zakerzade; Ching-Ho Chang; Kamalakar Chatla; Ananya Krishnapura; Samuel P Appiah; Jacki Zhang; Robert L Unckless; Justin P Blumenstiel; Doris Bachtrog; Kevin H-C Wei (PLoS Genetics)
The synaptonemal complex (SC) is a protein-rich structure essential for meiotic recombination and faithful chromosome segregation. Acting like a zipper to paired homologous chromosomes during early prophase I, the complex is a symmetrical structure where central elements are connected on two sides by the transverse filaments to the chromatin-anchoring lateral elements. Despite being found in most major eukaryotic taxa implying a deeply conserved evolutionary origin, several components of the complex exhibit unusually high rates of sequence turnover. This is puzzlingly exemplified by the SC of Drosophila, where the central elements and transverse filaments display no identifiable homologs outside of the genus. Here, we exhaustively examine the evolutionary history of the SC in Drosophila taking a comparative phylogenomic approach with high species density to circumvent obscured homology due to rapid sequence evolution. Contrasting starkly against other genes involved in meiotic chromosome pairing, SC genes show significantly elevated rates of coding evolution due to a combination of relaxed constraint and recurrent, widespread positive selection. In particular, the central element cona and transverse filament c(3)G have diversified through tandem and retro-duplications, repeatedly generating paralogs with novel germline activity. In a striking case of molecular convergence, c(3)G paralogs that independently arose in distant lineages evolved under positive selection to have convergent truncations to the protein termini and elevated testes expression. Surprisingly, the expression of SC genes in the germline is prone to change suggesting recurrent regulatory evolution which, in many species, resulted in high testes expression even though Drosophila males are achiasmic. Overall, our study recapitulates the poor conservation of SC components, and further uncovers that the lack of conservation extends to other modalities including copy number, genomic locale, and germline regulation. Considering the elevated testes expression in many Drosophila species and the common ancestor, we suggest that the activity of SC genes in the male germline, while still poorly understood, may be a prime target of constant evolutionary pressures driving repeated adaptations and innovations.